Design, flight dynamic analysis and hover control of a vertical take-off and landing micro air vehicle - Setiawan, Suhartono (2009)
A ducted fan Vertical Take-off and Landing (VTOL) Micro Air Vehicle (MAV) is developed. The vehicle is equipped with a wing that can be rotated in the pitch direction (variable incidence). This feature is expected to suppress the altitude loss during transition and to reduce the gust effect in hover. The selected configuration is capable to yield satisfactory aerodynamic performances and satisfy the static stability requirements in the cruise-flight. The variable-incidence wing feature is found to yield a higher lift and a lower drag at high angles of attack flight.